Clinical factors related to successful or unsuccessful cardioversion in the EdoxabaN versus warfarin in subjectS UndeRgoing cardiovErsion of Atrial Fibrillation (ENSURE‐AF) randomized trial. Issue 3 (15th April 2020) - Lip, Gregory Y. H.; Merino, Jose L.; Banach, Maciej; Al‐Saady, Naab; Jin, James; Melino, Michael; Winters, Shannon M.; Kozieł, Monika; Goette, Andreas
Abstract: Background: EdoxabaN versus warfarin in subjectS UndeRgoing cardiovErsion of Atrial Fibrillation evaluated use of nonvitamin K antagonist oral anticoagulant edoxaban vs enoxaparin‐warfarin in patients with nonvalvular atrial fibrillation undergoing electrical cardioversion. Hypothesis: To assess clinical factors related to successful or unsuccessful cardioversion. To evaluate whether differences in adverse events based on anticoagulation strategy may exist. Methods: In this multicenter prospective randomized open‐label blinded end‐point evaluation trial, 2199 patients were randomized to edoxaban 60 mg once daily (30 mg for creatinine clearance 15‐50 mL/min, weight ≤ 60 kg, and/or concomitant use of P‐glycoprotein inhibitor) or enoxaparin‐warfarin. Successful cardioversion was confirmed by 12‐lead electrocardiography‐documented sinus rhythm. Results: Cardioversion was successful in 1578 patients; in 355 patients, cardioversion was unsuccessful. Male, high body weight, high body mass index (BMI), coronary artery disease, concomitant aspirin, or prior statins use were more common in patients with unsuccessful cardioversion; international normalized ratio control did not differ by cardioversion success. On multivariate analysis, gender ( P < .05), body weight ( P = .0196) and BMI ( P = .0377) emerged as independent predictors of successful cardioversion. There were no significant differences in primary efficacy (a composite of stroke, systemic embolic event, myocardial infarction, and cardiovascular death during overall study period) regardless of cardioversion success. There were no significant differences in bleeding rates, regardless of cardioversion outcome; notwithstanding low numbers, edoxaban and enoxaparin‐warfarin did not differ. Conclusions: Male gender, higher mean weight and higher mean BMI were associated with unsuccessful cardioversion. Efficacy and safety outcomes were low and did not differ by cardioversion success.